Pengembangan Alat Tanam Benih Langsung Tipe Drum Seeder - Abdul Azis; Muhammad Farham Rifaldy Akhmad; Daniel Useng (Jurnal Agritechno, 2022)
Direct seeder is are a planting method that is used with a direct planting system using tools. However, the atabela that is used by the community in general still has problems such as the absence of a channel opening so that the seeds that fall are not in the specified channel, the absence of a ground leveler so that the land is inundated with water. The above constraints cause the growth and maintenance of rice that is not optimal. The design of atabela is expected to simplify the process of planting rice seeds by using simple technology to save time and effort. The part of the tool developed is that the groove opener functions as a place for the seeds to fall, the ground leveler functions to flatten the soil before the seeds are dropped and the hole coverings are used as a barrier to fall seeds where they are not wanted. The test results show that the parts of the tool are functioning properly, where the results obtained are 25 cm side spacing, 25-50 cm future spacing, 9-15 seeds yielding seeds and regularity of seeds entering the holes or grooves that have been made.